Konservatisme Akuntansi Memoderasi Hubungan Persistensi Laba dan Default Risk dengan Kualitas Laba : Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Non Keuangan Periode 2020–2022 - Erimina Halawa (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze and provide empirical evidence of the influence of earnings persistence variables on earnings quality, to analyze and provide empirical evidence of the influence of default risk variables on earnings quality, to analyze and empirical evidence that accounting conservatism moderates the effect of earnings persistence on earnings quality, to analyze and empirical evidence of conservatism accounting moderates the effect of default risk on earnings quality. This type of research is associative quantitative research, using secondary data. The data analysis method used is a panel data regression test using Microsoft Excel and Eviews 12 applications. The population in this study are all companies listed on the Indonesian Non-Financial Stock Exchange for the period 2020 - 2022. The data collection technique in this research is a purposive sampling technique with The results of the 842 research population were 89 companies with 3 years of observation, so that 267 data were processed in this research. The research results show that earnings persistence influences earnings quality, default risk influences earnings quality, accounting conservatism strengthens the relationship between earnings persistence and earnings quality and accounting conservatism is also able to strengthen the relationship between default risk and earnings quality.